2021
DOI: 10.3390/en14196335
|View full text |Cite
|
Sign up to set email alerts
|

Using the Modified Resistivity–Porosity Cross Plot Method to Identify Formation Fluid Types in Tight Sandstone with Variable Water Salinity

Abstract: It is generally difficult to identify fluid types in low-porosity and low-permeability reservoirs, and the Chang 8 Member in the Ordos Basin is a typical example. In the Chang 8 Member of Yanchang Formation in the Zhenyuan area of Ordos Basin, affected by lithology and physical properties, the resistivity of the oil layer and water layer are close, which brings great difficulties to fluid type identification. In this paper, we first analyzed the geological and petrophysical characteristics of the study area, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Determination of the type of fluid at low resistivity and low contrast determines the fluid contained in the reservoir with the phenomenon of low resistivity low contrast. In a study conducted by Yang, et al 2021 entitled "Using the modified Resistivity-porosity cross plot method to identify formation fluid type in tight sandstone with variable water salinity." They conducted an analysis of the type of fluid contained in the low resistivity low contrast zone using a cross plot between porosity and resistivity parameters which can be seen in Figure 1 [15].…”
Section: Fluid Type Determinationmentioning
confidence: 99%
“…Determination of the type of fluid at low resistivity and low contrast determines the fluid contained in the reservoir with the phenomenon of low resistivity low contrast. In a study conducted by Yang, et al 2021 entitled "Using the modified Resistivity-porosity cross plot method to identify formation fluid type in tight sandstone with variable water salinity." They conducted an analysis of the type of fluid contained in the low resistivity low contrast zone using a cross plot between porosity and resistivity parameters which can be seen in Figure 1 [15].…”
Section: Fluid Type Determinationmentioning
confidence: 99%
“…The total oil resources in the basin are about 8.6 billion tons, ranking fourth in the China. [20][21][22][23][24] After years of exploration and research, it has been found that the Triassic Yanchang Formation reservoirs in Dingbian, Jiyuan, Huanxian, Ansai and other areas in the basin contain abundant low-resistivity oil and gas resources. 25 , 26 The Yanchang Formation reservoir has complex pore structure, low permeability, and the growth of low-resistivity oil pays, which has brought great obstacles to exploration and development.…”
Section: Introductionmentioning
confidence: 99%
“…With the in-depth study and application of statistical analysis and complex network theory, crossplot [28][29][30] and ordinal pattern transition networks (OPTN) [31][32][33][34] are emerging as major tools for nonlinear time series interrelationship analysis and are finding meaningful applications in the analysis of experimental data in a variety of research fields. Crossplot is a graphical representation of time series in the Cartesian plane.…”
Section: Introductionmentioning
confidence: 99%